SISTEM PERHITUNGAN HPP DENGAN METODE FULL COSTING BERBASIS CODEIGNITER PADA USAHA KECIL MENENGAH - Kasih Purwantini; Tantik Sumarlin (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract Small and medium businesses in the area of Semarang in managing onventional financial problems. In relation to the development of technology, small and medium entrepreneurs have not yet utilized information technology optimally. The calculation of the price of production is also still being done conventionally. The aim is to carry out this research to help small and medium-sized businesses in the process of calculating the cost of production by using the hp calculation system. Hpp calculation method using codeigniter based full costing method. Systems development method by using search and devepoment methods. The steps in research and development include Research and Information Collection, Planning, Developing Preliminary Forms of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision, Operational Field Testing, Final Product Revision, and Dissemination and Implementation. Based on the survey, the hpp calculation system with a codeigniter-based full costing method can be accepted and makes it easier for small and medium businesses in managing their finances specifically in the hpp calculation. The HPP calculation system makes financial management performance more time and energy efficient. Financial reports from the HPP calculation system become more accurate. The HPP calculation system prevents unexpected fraud. HPP calculation system is equipped with security.